Предмет: Алгебра, автор: dilnaz8021

а) b1=0,(3)
q =  \sqrt{3}
S6-?

б)
b1 =   {7}^{ - 1}
q =  \sqrt{7}
S6-?​

Ответы

Автор ответа: zinaidazina
1

а)  

b_1=0,(3)=\frac{3}{9} =\frac{1}{3}

q=\sqrt{3}

S_6-?

Решение

S_n=\frac{b_1(1-q^n}{1-q}

S_6=\frac{\frac{1}{3}*(1-(\sqrt{3})^6)}{1-\sqrt{3}}=\frac{1-(\sqrt{3})^6}{3*(1-\sqrt{3})}=\frac{1-3^3}{3*(1-\sqrt{3})}=\frac{1-27}{3*(1-\sqrt{3})}=\frac{-26}{3*(1-\sqrt{3})}=

  =\frac{-26*(1+\sqrt{3} )}{3*(1-\sqrt{3})*(1+\sqrt{3} )}=\frac{-26*(1+\sqrt{3} )}{3*(1^2-(\sqrt{3})^2)}= \frac{-26*(1+\sqrt{3} )}{3*(1-3)}=  \frac{-26*(1+\sqrt{3} )}{3*(-2)}= \frac{13(1+\sqrt{3} )}{3}

Ответ:    \frac{13(1+\sqrt{3} )}{3}

б)

b_1=7^{-1}=\frac{1}{7}

q=\sqrt{7}

S_6-?

Решение

S_n=\frac{b_1(1-q^n}{1-q}

S_6=\frac{\frac{1}{7}*(1-(\sqrt{7})^6}{1-\sqrt{7} }=\frac{1*(1-(\sqrt{7})^6}{7*(1-\sqrt{7}) }=\frac{1-7^3}{7*(1-\sqrt{7}) }=\frac{1-343}{7*(1-\sqrt{7}) }=\frac{-342*(1+\sqrt{7} )}{7*(1-\sqrt{7})(1+\sqrt{7} ) }=

=\frac{-342*(1+\sqrt{7} )}{7*(1^2-(\sqrt{7})^2) }=\frac{-342*(1+\sqrt{7} )}{7*(1-7) }=\frac{-342*(1+\sqrt{7} )}{7*(-6) }=\frac{57*(1+\sqrt{7} )}{7}

Ответ:    \frac{57*(1+\sqrt{7} )}{7}

Похожие вопросы
Предмет: Алгебра, автор: DaEmOn2013
Предмет: Литература, автор: jopka3000